Acceleration of bainitic transformation by introducing AlN in medium carbon steel. Issue 2 (22nd January 2019) - Zhao, Xiaojie; Yang, Zhinan; Zhang, Fucheng; Long, Xiaoyan; Chen, Chen
ABSTRACT: Shortening the austempering time for bainitic transformation is beneficial for the application of high-performance bainitic steel, which has attracted lots of attentions from materials researchers. It is interesting to find that adding nitrogen, ∼210 ppm, in a medium carbon steel can effectively accelerate the bainitic transformation process. Analysis results reveal that the heterogeneous nucleation sites provided by AlN particles should be mainly responsible for the accelerated bainitic transformation.